Predictors of Dependency in Instrumental Activities of Daily Living Among Community Dwelling Elderly in A Rural Field Practice Area of a Tertiary Care Hospital in Chengalpattu District, Tamilnadu, India- A Cross Sectional Study - M, Lavanya; MVM, Pradeep; Hussain, Aamina; Anantharaman VV; M, Logaraj (National Journal of Community Medicine, 2025)
Background: Longer lifespans of elderly are associated with chronic illnesses that impair functioning, making it harder to carry out daily activities and making assistance necessary. The aim was to estimate the prevalence of dependence in Instrumental Activities of Daily Living (IADL) among elderly and to determine its sociodemographic and health related predictors. Methodology: This cross-sectional study was conducted among elderly in Chengalpattu district from December 2023 to May 2024. Sample size was determined by multistage random sampling. A semi-structured questionnaire consisting of sociodemographic details and Lawton scale to assess dependence were used to collect data. Data was entered in Ms Excel and analysed using SPSS version 26. Results: Mean age of participants was 67.4 ± 7.4 years. 131 (43.7%) of them were at risk of malnutrition and 83 (27.7%) were malnourished. Majority (n=178,59.3%) experienced increased IADL dependency. Binary logistic regression analysis showed increasing age, lower socioeconomic status, Divorced/Widowed/Unmarried, smoking and tobacco use, hospitalizations within previous year were significant predictors of IADL dependency. Conclusions: The study concluded that a considerable proportion of our study population was suffering from IADL dependency (59.3%), with majority demonstrating mild to moderate degree of dependency. To prevent disease in its early stages, arrangements can be made for community-based extensive geriatric health assessments.